Nigerian doctors' experiences of guideline-based asthma management: a qualitative study - Obianuju B. Ozoh; Sandra Dede; Joy Eze; Kevin Mortimer; Martha Chinouya (Inishmore Laser Scientific Publishing Ltd, 2022)
# Background The Global Initiative for Asthma (GINA) report sets out an updated evidence-based strategy for asthma management. Little is known about how this report is perceived and implemented in low-income and middle-income countries (LMICs) like Nigeria. We explored the experiences of asthma management as informed by the current GINA guideline among doctors in Lagos, Nigeria. # Methods Using a qualitative research approach, in-depth interviews were conducted among doctors in Lagos, Nigeria to explore their experiences of asthma management in the context of the current GINA report. The thematic framework approach was used for data analysis. # Results Eleven doctors aged 28-46 years (five general practitioners (GPs) and six family physicians (FPs) took part. Four overarching themes were identified: (i) *knowledge of, and attitude towards the GINA strategy* -- whilst most doctors were aware of the existence of the GINA report, there was limited knowledge about its content including current recommendations for mild asthma treatment; (ii) *asthma diagnosis and treatment* -- there was limited access to lung function testing facilities, and its role in asthma diagnosis was underappreciated; (iii) *barriers to managing asthma according to GINA recommendations* -- these included complexity of the GINA report, unavailability and unaffordability of asthma medicines and poor patient adherence to medications, driven by socio-cultural factors; and (iv) *enablers of GINA-recommended asthma management* -- improvement in asthma education for doctors and the general population and better access to diagnostic tests and medicines. # Conclusions Whilst there was awareness of the existence of the GINA report, there was limited knowledge about its content and several barriers to its implementation were reported. Education about the GINA report, investment in diagnostic and treatment services and simplification of recommendations were identified as possible solutions.